Bdellovibrio and like organisms: current understanding and knowledge gaps of the smallest cellular hunters of the microbial world. (4th July 2022) - Ezzedine, Jade A.; Desdevises, Yves; Jacquet, Stéphan
Abstract: Almost sixty years ago, Bdellovibrio and like organisms (BALOs) were discovered as the first obligate bacterial predators of other bacteria known to science. Since then, they were shown to be diverse and ubiquitous in the environment, and to bear astonishing ecological, physiological, and metabolic capabilities. The last decade has seen important strides made in understanding the mechanistic basis of their life cycle, the dynamics of their interactions with prey, along with significant developments towards their use in medicine, agriculture, and industry. This review details these achievements, identify current understanding and knowledge gaps to encourage and guide future BALO research.